2023
DOI: 10.1093/asj/sjad051
|View full text |Cite
|
Sign up to set email alerts
|

A Computed Tomographic Investigation of the Ophthalmic Artery Volume and Its Relevance to Soft Tissue Filler Injections

Abstract: Background The measured intra-arterial volume of cadaveric ophthalmic arteries was used for safety recommendations during facial soft tissue filler injections. However, its clinical practicability and model applicability has become questionable. Objectives To measure the volume of the ophthalmic artery in living individuals by utilizing computed tomography (CT) imaging technology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…It has to be emphasized that despite previous studies have measured the intra-arterial volume of the ophthalmic artery (between 0.1 and 0.2 cc), 11,12 Based on the results obtained it can be concluded that the constant needle motion technique is not a safer procedure when administering facial soft tissue filler injections. The odds of encountering an artery within the covered soft tissue volume and the odds of injecting a volume into the arterial blood stream that is greater than zero increases with the number of performed injection passes.…”
Section: F I G U R Ementioning
confidence: 87%
See 3 more Smart Citations
“…It has to be emphasized that despite previous studies have measured the intra-arterial volume of the ophthalmic artery (between 0.1 and 0.2 cc), 11,12 Based on the results obtained it can be concluded that the constant needle motion technique is not a safer procedure when administering facial soft tissue filler injections. The odds of encountering an artery within the covered soft tissue volume and the odds of injecting a volume into the arterial blood stream that is greater than zero increases with the number of performed injection passes.…”
Section: F I G U R Ementioning
confidence: 87%
“…It has to be emphasized that despite previous studies have measured the intra‐arterial volume of the ophthalmic artery (between 0.1 and 0.2 cc), 11,12 no threshold value for soft tissue filler injections is currently available. No study to date has clinically or theoretically investigated whether there is such lower threshold value, and it therefore must be concluded that any volume of intra‐arterially placed soft tissue filler greater than zero is detrimental.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The intent of this paper by Lin et al is, first, to determine more accurately the average volume of the ophthalmic artery in 40 living individuals (80 ophthalmic arteries) by undertaking a detailed contrast agent–enhanced computed tomography topographic study. 1 The authors feel that measuring the ophthalmic artery volume in cadaveric specimens has multiple limitations, and therefore inaccuracies, making it difficult to reach definite conclusions based on such studies.…”
mentioning
confidence: 99%